2013
DOI: 10.4028/www.scientific.net/amm.393.688
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Active Force Control Application to Twin Rotor Mimo System

Abstract: This paper reports a current study on modeling and simulation of adaptive Active Force Control (AFC) based scheme embedded with an artificial neural network (ANN) and/or fuzzy logic (FL) in response manipulations of the twin rotor multi-input multi-output (MIMO) system (TRMS). TRMS is well known for its non-linear behaviour and common classical control scheme such as Proportional-Integral-Derivative (PID) would not be adequate to compensate disturbances. The disturbances in this case were as the results of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The basic idea of the AFC technique is the appropriate estimation of the mass/inertia parameter of the dynamical system and measurements of the acceleration and force/torque signals generated by the system as shown in Figure 13. Some research works have been reported in [176], [177] that analytically utilized the AFC-based technique with a PID controller to control the TRMS model and compensate for the applied disturbances. The works presented a comparative study of system performance by analyzing the output responses based on PID-AFC, PID-AFC-ANN, and PID-AFC-FL schemes.…”
Section: External Disturbancesmentioning
confidence: 99%
“…The basic idea of the AFC technique is the appropriate estimation of the mass/inertia parameter of the dynamical system and measurements of the acceleration and force/torque signals generated by the system as shown in Figure 13. Some research works have been reported in [176], [177] that analytically utilized the AFC-based technique with a PID controller to control the TRMS model and compensate for the applied disturbances. The works presented a comparative study of system performance by analyzing the output responses based on PID-AFC, PID-AFC-ANN, and PID-AFC-FL schemes.…”
Section: External Disturbancesmentioning
confidence: 99%
“…Regarding rotorcraft UAVs [18], some research works have been reported in [19] and [20], which combined the AFC strategy analytically with a PID controller to stabilize the 2-DOF helicopter model and compensate for the disturbances. The simulated results showed the effectiveness and robustness of the AFC-based technique.…”
Section: Introductionmentioning
confidence: 99%